Metabolic responses of rice cultivars with different tolerance to combined drought and heat stress under field conditions - Lawas, Lovely Mae F.; Li, Xia; Erban, Alexander; Kopka, Joachim; Jagadish, Krishna S.V.; Zuther, Ellen; Hincha, Dirk K. (Oxford University Press, 2019)
Rice is susceptible to both drought and heat stress, in particular during flowering and grain filling, when both grain yield and quality may be severely compromised. However, under field conditions, these 2 stresses rarely occur separately. Under well-watered conditions, plants avoid heat stress by transpirational cooling, while this is not possible under drought conditions. Although investigating combined drought and heat stress is clearly more agronomically relevant than analyzing the effects of the single stresses, only a few studies of this stress combination, in particular under field conditions, have been published Three rice cultivars differing in drought and heat tolerance were grown in the field under control and drought conditions in 3 consecutive years. Drought was applied either during flowering or during early grain filling and resulted in simultaneous heat stress, leading to reduced grain yield and quality. Analysis by gas chromatography−mass spectrometry showed distinct metabolic profiles for the 3 investigated organs (flag leaves, flowering spikelets, developing seeds). The metabolic stress responses of the plants also strongly differed between cultivars and organs. Correlation analysis identified potential metabolic markers for grain yield and quality under combined drought and heat stress from both stress-regulated metabolites and from metabolites with constitutive differences between the cultivars Gas chromatography−mass spectrometry resolved metabolic responses to combined drought and heat stress in different organs of field-grown rice. The metabolite profiles can be used to identify potential marker metabolites for yield stability and grain quality that are expected to improve breeding efforts towards developing rice cultivars that are resilient to climate change.